DMOs and Social Media Crisis Communication in Low-Responsibility Crisis: #VisitPortugal Response Strategies During COVID-19 - Mariana Casal-Ribeiro; Rita Peres; Inês Boavida-Portugal (Tourism and Hospitality)
Guided by the situational crisis communication theory (SCCT), this study explores how a destination marketing organization (DMO) managed crisis communication during a prolonged low-responsibility crisis. It analyzes the production process of crisis communication, the crisis communication content shared on Facebook to protect the destination’s image during COVID-19, and evaluates which crisis response strategies led to higher audience engagement. This study used a single instrumental case study with an exploratory sequential approach. A semi-structured interview was conducted with Visit Portugal’s Communication and Digital Marketing Director. Then, Facebook content from Visit Portugal, posted between 1 January 2020 and 5 May 2023, was collected and analyzed. By analyzing the DMO’s crisis communication workflow, decision-making processes, and content shared on social media, it was found that secondary response strategies effectively safeguarded and improved the destination’s image, leading to higher audience engagement. This study provides DMOs with valuable insights into the development of effective crisis communication strategies when navigating low-responsibility crises.